Quantifying the role of urbanization on airflow perturbations and dunefield evolution. Issue 5 (24th May 2017) - Smith, Alexander B.; Jackson, Derek W. T.; Cooper, J. Andrew G.; Hernández‐Calvento, L.
Abstract: Rapid urban development has been widespread in many arid regions of the world during the Anthropocene. Such development has the potential to affect, and be affected by, local and regional dunefield dynamics. While urban design often includes consideration of the wind regime, the potential impact of construction on the surrounding environment is seldom considered and remains poorly understood. In this study, regional airflow modeling during successive stages of urbanization at Maspalomas, Gran Canaria, Spain, indicates significant and progressive flow perturbations that have altered the adjacent dunefield. Significant modifications to the boundary layer velocity, mean wind directionality, turbulence intensity, and sediment flux potential are attributed to the extension of the evolving urban geometry into the internal boundary layer. Two distinct process/response zones were identified: (1) the urban shadow zone where widespread dune stabilization is attributed to the sheltering effect of the urban area on surface wind velocity; and (2) the acceleration zone where airflow is deflected away from the urbanized area, causing an increase in sediment transport potential and surface erosion. Consistent coherent turbulent structures were identified at landform and dunefield scales: counter‐rotating vortices develop in the lee‐side flow of dune crests and shedding off the buildings on the downwind edge of the urban area. This study illustrates the direct geomorphic impact of urbanization on aeolian dunefield dynamics, a relationship that has received little previous attention. The study provides a template for investigations of the potential impact of urbanization in arid zones. Key Points: Human development in arid dune environments significantly alters regional airflow patterns that modify adjacent dunefield dynamics Progressive urbanization has led to divergent evolution of both increased erosion and stability at Maspalomas dunfield, Gran Canaria, Spain Urbanization has significantly altered the sediment dynamics across the active dunes surfaces causing an acceleration of erosion